Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Dinas Pangan Kota Gorontalo - Podungge, Robiyati; Monoarfa, Valentina; Asi, Lisda L.; Asnawi, Melan Angriani; Sjahbuddin, Indah Rahmadanti (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the effect of Work Environment and Work Stress on Employee Performance at the Gorontalo City Food Service. The sample in this study was 47 employees. The data analysis techniques used in this study were descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis testing.The results of this study indicate that (1) The work environment has a positive and significant effect on employee performance at the Gorontalo City Food Service by 54.5%. (2) Work Stress has a positive and significant effect on employee performance at the Gorontalo City Food Service by 3.41%. so partially the variables of work environment and work stress have a positive and significant effect on employee performance at the Gorontalo City Food Service. (3) Work Environment and Work Stress simultaneously have a positive and significant effect on employee performance at the Gorontalo City Food Service with a determination coefficient of 57.9%. While the remaining 42.1% can be influenced by other variables not examined in this study such as competency factors, performance allowances, organizational commitment, organizational culture and performance training.